Some Computational Aspects of Vehicle Shell Frames Optimization Subjected to Fatigue Life - Saga, Milan; Kopas, Peter; Vasko, Milan (Communications - Scientific letters of the University of Zilina, 2010)
The paper deals with the implementation of the fatigue damage conditions into structural optimization process. The study considers a shell finite element structural analysis in conjunction with the multiaxial rainflow counting, the fatigue damage prediction and naturally the sizing (element thickness) optimizing design. We will analyze FE models under random excitation in time domain. The presented optimizing approach will be implemented into solution program compiled in Matlab.